Effect of irrigation regimes and nutrient management on soil water dynamics, evapo-transpiration and yield of wheat (Triticum aestivum) in Vertisol - HATI, K M; MANDAL, K G; MISRA, A K; GHOSH, P K; ACHARYA, C L (The Indian Journal of Agricultural Sciences, 2014)
An experiment was conducted with wheat (Triticum aestivum L. emend. Fiori & Paol.) grown on a heavy clay soil (Vertisol) for winter season of 1998-99 and 1999-2000. to find out the effect of varying levels of irrigation regimes and nutrients oil soil water dynamics, evapo-transpiration (ET). water-use efficiency and grain yield of wheat. The fertilized plots retained less moisture in the soil profile at harvest than the unfertilized ones. Moisture extraction (%) from the top 30 cm soil increased with the increase in irrigation level (from 33.6% in no irrigation to 50.2% in 3 irrigations), while from deeper layers (60-120 cm) it was higher in the manured and fertilized plots (37%) than the plots where no nutrients were applied (24.5%). Evapo-transpiration throughoutthe growth stages was higher for irrigated plots (303.0 mm) than unirrigated plots (148.7 mm). However, in the lin irrigated plots evapo-transpiration reached its peak earlier (between 75 and 90 days after sowing) compared with the irrigated plots (between 90 and 105 days after sowing). At a particular irrigation level. evapo-trunspiration was higher in the fertilized and manured plots than the unfertilized plots at all the stages of growth. Grain yield increased signitieantly with the increase in irrigation levels (89.2 and 103.7%) by 3 irrtglttions over no irrigation in first and second year respectively) and with integrated application of fertilizer and farmyard manure (138.5 and 123.0% by recommended dose of NPK + farmyard manure @ 10 tonnes/ha over the control in first Bnd second year respectively). The evapo-transpiration showed a linar relationship (R2 0.71) with the grain yield. The water-use efficiency was highest at no irrigation, followed by 2 and 3 irrigations treatments, whereas iit was higher in the fertilized and manured plots than that in the unfertilized plots.